Esterification catalyzed by an efficient solid acid synthesized from PTSA and UiO-66(Zr) for biodiesel production. (1st July 2021) - Li, Hui; Han, Zhihao; Liu, Fengsheng; Li, Guoning; Guo, Min; Cui, Ping; Zhou, Shoujun; Yu, Mingzhi
Abstract : PTSA is successfully inserted in UiO-66(Zr) without destroying its original structure (UiO-G), the maximum conversion of 91.3% is achieved and UiO-G could remarkably reduce the activation energy of esterification to 28.61 kJ mol –1 . Abstract : p -Toluenesulfonic acid (PTSA) is a typical homogeneous acid for biodiesel production. Due to the shortcomings of high deliquescence and non-recyclability, it is necessary to synthesize a recyclable solid acid. For the sake of this, UiO-66(Zr) is used to support PTSA through defect coordination, and four different preparation routes are compared. The obtained catalyst (UiO-G) is characterized with thermogravimetry analysis (TG), X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), pyridine FTIR spectroscopy (py-FTIR), nitrogen adsorption–desorption, and base titration. In addition, the effects of esterification parameters on conversion are investigated to obtain the optimal conditions. To further verify the high catalytic activity of UiO-G, the kinetic model of solid–liquid–liquid esterification is established, in which the kinetic parameters of activation energy, reaction order, and exponential factor are calculated. Results indicate the PTSA is successfully inserted in UiO-66(Zr) without destroying its original structure. With that, the maximum conversion of oleic acid to biodiesel of 91.3% is achieved with a molar ratio of methanol/oleic acid of 12 and a catalyst amount of 8 wt% at 70 °C for 2 h. Moreover, UiO-G could remarkably reduce the activation energy, where the activation energy is 28.61 kJ mol −1, the average reaction order is 1.51, and the pre-exponential factor is 29.11 min −1 .